2010
DOI: 10.1071/pc100144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ungulate Management on Vegetation at Hakalau Forest National Wildlife Refuge, Hawai?i Island

Abstract: We compiled and analysed data from 1987?2004 on vegetation monitoring during feral ungulate management at Hakalau Forest National Wildlife Refuge, a tropical montane rainforest on the island of Hawai?i. All areas in the study had previously been used by ungulates, but cattle (Bos taurus) were removed and feral pig (Sus scrofa) populations were reduced during the study period. We monitored six line-intercept transects, three in previously high ungulate use areas and three in previously low ungulate use areas. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Refuge scientists are also particularly interested in ichneumonid populations because non-native parasitoid wasps may contribute to the decline of bird populations through reduction of important insect prey [25]. Non-native species are an important consideration for most Hawaiian restoration efforts [28], [46]; in HFNWR, particular non-natives species of concern include feral pigs ( Sus scrofa ) [47], several highly invasive plant species, and the approximately 25% of the avian population comprised of non-native birds [48], [49].…”
Section: Discussionmentioning
confidence: 99%
“…Refuge scientists are also particularly interested in ichneumonid populations because non-native parasitoid wasps may contribute to the decline of bird populations through reduction of important insect prey [25]. Non-native species are an important consideration for most Hawaiian restoration efforts [28], [46]; in HFNWR, particular non-natives species of concern include feral pigs ( Sus scrofa ) [47], several highly invasive plant species, and the approximately 25% of the avian population comprised of non-native birds [48], [49].…”
Section: Discussionmentioning
confidence: 99%
“…Diet analysis shows that pigs will eat almost any organic substance (Schley & Roper, 2003) including plants, birds, amphibians, and other mammals. Managing wild pigs is important given their influence on actively protected areas, such as wildlife refuges, national forests, and parks, through their rapid consumption of flora and fauna (Campbell & Long, 2009;Hess, Jeffrey, Pratt, & Ball, 2010;Singer, Otto, Tipton, & Hable, 1981). Other impacts to ecosystems that are caused by wild pigs include pathogen shedding into water sources (Hampton, Spencer, Elliot, & Thompson, 2006;Jay et al, 2007), pathogen spillover (Wu et al, 2012), and viral reassortment (Hall et al, 2008;Kida et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The upper part of the refuge was converted to cattle grazing lands by the mid‐1800s. In the early 1990s, portions of the upper refuge were fenced, all cattle were removed and the feral pig population has been controlled (Hess, Jeffrey, Ball, & Babich, ; Hess, Jeffrey, Pratt, & Ball, ). Leopold, Hess, Kendall, and Judge () reported that between 2010 and 2015 more than 1,600 pigs were removed from Hakalau Forest National Wildlife Refuge and that traces of pig activity were still observed in 2015.…”
Section: Methodsmentioning
confidence: 99%